2007
DOI: 10.1111/j.1471-4159.2007.04884.x
|View full text |Cite
|
Sign up to set email alerts
|

Necrostatin‐1 protects against glutamate‐induced glutathione depletion and caspase‐independent cell death in HT‐22 cells

Abstract: Glutamate, a major excitatory neurotransmitter in the CNS, plays a critical role in neurological disorders such as stroke and Parkinson's disease. Recent studies have suggested that glutamate excess can result in a form of cell death called glutamate-induced oxytosis. In this study, we explore the protective effects of necrostatin-1 (Nec-1), an inhibitor of necroptosis, on glutamate-induced oxytosis. We show that Nec-1 inhibits glutamate-induced oxytosis in HT-22 cells through a mechanism that involves an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
122
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(133 citation statements)
references
References 46 publications
9
122
0
2
Order By: Relevance
“…The flow cytometric detection of Annexin-V (AnxV) and propidium iodide (PI) suggested that all HT-22 transfectants followed a necrotic fate (AnxV + /PI + and AnxV − /PI + ) rather than an apoptotic fate after glutamate challenge; this necrotic response was clearly enhanced following the knockdown of HuR (Figure 4a). The pancaspase inhibitor zVAD-FMK did Figure 4f); these observations confirmed that apoptosis is not the predominant form of death response in these cells [28][29][30] nor it comes into effect because of HuR's loss. In contrast, a beneficial effect of the RIP-kinase 1 inhibitor necrostatin-1 (Nec-1) in HT-22 cells 29 was partially maintained in HuR lo cells, suggesting that necrotic/necroptotic pathways are maintained in the absence of HuR (Figure 4b).…”
Section: Elavl1supporting
confidence: 55%
See 1 more Smart Citation
“…The flow cytometric detection of Annexin-V (AnxV) and propidium iodide (PI) suggested that all HT-22 transfectants followed a necrotic fate (AnxV + /PI + and AnxV − /PI + ) rather than an apoptotic fate after glutamate challenge; this necrotic response was clearly enhanced following the knockdown of HuR (Figure 4a). The pancaspase inhibitor zVAD-FMK did Figure 4f); these observations confirmed that apoptosis is not the predominant form of death response in these cells [28][29][30] nor it comes into effect because of HuR's loss. In contrast, a beneficial effect of the RIP-kinase 1 inhibitor necrostatin-1 (Nec-1) in HT-22 cells 29 was partially maintained in HuR lo cells, suggesting that necrotic/necroptotic pathways are maintained in the absence of HuR (Figure 4b).…”
Section: Elavl1supporting
confidence: 55%
“…The pancaspase inhibitor zVAD-FMK did Figure 4f); these observations confirmed that apoptosis is not the predominant form of death response in these cells [28][29][30] nor it comes into effect because of HuR's loss. In contrast, a beneficial effect of the RIP-kinase 1 inhibitor necrostatin-1 (Nec-1) in HT-22 cells 29 was partially maintained in HuR lo cells, suggesting that necrotic/necroptotic pathways are maintained in the absence of HuR (Figure 4b).…”
Section: Elavl1supporting
confidence: 55%
“…Consequently, RIP1-deficient MEFs are resistant to MNNG-induced PCD (55). The relationship between RIP1 and AIF has been fully confirmed, by using necrostatin-1 inhibitor in other necroptotic systems, such as retinal detachmentinduced photoreceptor necrosis or glutamate-induced oxytosis in hippocampal HT-22 cells (71,72).…”
Section: Aif-mediated Caspase-independent Necroptosismentioning
confidence: 71%
“…More recently, new forms of necroptosis have been unveiled (67)(68)(69)(70)(71). One of them is the pathway scrutinized in our laboratory: alkylating DNA damage (MNNG)-mediated PCD (11,33,39,51).…”
Section: Aif-mediated Caspase-independent Necroptosismentioning
confidence: 99%
“…There is no known direct antioxidant effect of necrostatin, but it does modulate redox mechanisms in experimental systems (Xu et al, 2007). Necrostatin increases glutathione levels and decreases ROS production (Xu et al, 2007), blocks nitric oxide-mediated cell necrosis and mitochondrial ROS production (Davis et al, 2010) and may also delay the opening of mitochondrial permeability transition pore (Lim et al, 2007). These effects may be reflected in the decrease in protein oxidation in the first 24 hours and the subsequent delayed appearance of neuroprotection after HI and necrostatin administration in our model.…”
Section: Discussionmentioning
confidence: 87%